The Legal Consequences of Nominee Arrangements under the Basic Agrarian Law and Supreme Court Circular Number 10 of 2020, along with the Roles of Notary in Minimizing the Creation of Nominee Arrangement Deeds - Fitria Rahmawati; Albertus Sentot Sudarwanto; Lego Karjoko (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study examines the differences in the legal consequences of nominee arrangement in the Basic Law of Agaria and the Supreme Court Circular Number 10 of 2020 which will be viewed from the perspective of certainty and justice. The deed of nominee arrangement cannot be separated from the notary since only a notary can formulate it in the form of an authentic deed, so the author also examines the notary's role in minimizing the making of a deed of nominee arrangement. This research is normative and evaluative and uses primary and secondary legal materials. The technique of collecting legal materials uses the library study technique, and the technique of analyzing legal materials uses the deductive syllogism method. The study results show that the Basic Law of Agaria provides more justice and legal certainty than the Supreme Court Circular, so the rules on nominee arrangement in the Supreme Court Circular shouldn’t be enforced. The role of notary in minimizing the rampant nominee arrangement cannot be separated from the support and role of the Notary Supervisory Board to guide a preventive and repressive effort to strengthen a notary's morals and integrity patterns. Furthermore, this writing hopes that the Supreme Court revokes the rules relating to nominee arrangement. Another hope is that notary can actively prioritize their moral integrity to provide legal counseling and reject the creation of deeds containing nominee arrangement.